Notes on the leaf insects of the genus Phyllium of Sumatra and Java, Indonesia, including the description of two new species with purple coxae (Phasmatodea, Phylliidae) - Royce T. Cumming; Sarah Bank; Stephane Le Tirant; Sven Bradler (ZooKeys, 2020)
Within the last two years, the leaf insects of the genus Phyllium of both the islands of Java and Sumatra have been reviewed extensively based on morphological observations. However, cryptic species which cannot be differentiated morphologically may be present among the various populations. Since it has frequently been demonstrated that analyses based on molecular data can bring clarity in such cases, we conducted a phylogenetic analysis based on three genes (nuclear gene 28S and mitochondrial genes COI and 16S) from the Phyllium species of these islands. The results show distinct molecular divergence for several populations and suggest the presence of two new cryptic species, morphologically inseparable from Phyllium hausleithneri Brock, 1999. From Sumatra, the population originally thought to be a range expansion for Phyllium hausleithneri, is now here described as Phyllium nisus sp. nov., with the only consistent morphological difference being the color of the eggs between the two populations (dark brown in P. hausleithneri and tan in P. nisus sp. nov.). Further, an additional population with purple coxae from Java was morphologically examined and found to have no consistent features to separate it morphologically from the other purple coxae species. This cryptic species from Java was however shown to be molecularly distinct from the other purple coxae populations from Sumatra and Peninsular Malaysia and is here described as Phyllium gardabagusi sp. nov. In addition, Phyllium giganteum is here officially reported from Java for the first time based on both historic and modern records of male specimens.